Sternal Fracture in Children: Diagnosis by Ultrasonography - Sesia, Sergio B.; Prüfer, Friederike; Mayr, Johannes (European Journal of Pediatric Surgery Reports, 2017)
Because of its subcutaneous location, the sternum can be examined sonographically using a linear scanner. We report about two children who experienced blunt chest trauma. Anterior–posterior chest X-rays were normal. Ultrasonic imaging confirmed a fracture of the sternum with dorsal displacement of the distal fragment (by 0.97 cm) in the first child and a transverse fracture of the body of the sternum without displacement in the second child. In both children, pericardial effusion was excluded by sonography. The displaced fracture of the sternum was confirmed by magnetic resonance imaging (MRI), which ruled out concomitant injuries of the soft tissues adjacent to the sternum. Both sternum fractures were managed nonoperatively. These cases serve to emphasize the importance of sonography that represents an ionizing radiation free, noninvasive, efficient, and safe imaging modality to diagnose fractures of the sternum in children while also enabling the assessment of the pericardium.
Keywords: ultrasonography; children; sternum fracture; ultrasound